Years of experience is more effective in defining experts in the gaze analysis of laparoscopic suturing task than task duration. (October 2021) - Maeda, Yoshitaka; Oiwa, Kosuke; Matsumoto, Shiro; Nozawa, Akio; Kawahira, Hiroshi
Abstract: In this study, the relationship between gaze patterns, task duration, and years of experience, which are commonly used to define and evaluate expert surgeons in laparoscopic surgery, was identified. Ten surgeons with 1–28 years of experience and six inexperienced students were included. Subjects used forceps to repeat the task of suturing a suture pad. Each subject wore an eye-marking recorder, and gaze points were recorded and analyzed. No significant relationship between task duration and gaze pattern was observed. However, there was a significant relationship between a surgeon's years of experience and the percentage of time spent gazing at the forceps. Subjects with more years of experience operated without looking at the forceps and fixed their gaze on the operational target. Therefore, when analyzing laparoscopic gazing patterns, it may be more appropriate to define an "expert" based on the years of experience rather than task duration. Highlights: ● Definition of experts suitable for gaze pattern analysis in laparoscopic surgery ● Relationship between task duration, years of experience, and gaze patterns ● No significant relationship was found between task duration and gaze patterns ● Years of experience and gaze patterns were significantly related